Identifying Patterns in a Documentary-Convergence: Courage in a Crisis - Chhetri, Tek Bahadur (Saptagandaki Journal, 2022)
This paper explores how the technical aspects of filming are involved in making the Documentary-Convergence: Courage in a Crisis in relation to its overarching theme of global solidarity during the pandemic. For this analysis, my study largely depends on textual analysis of the film with the help of the analytical tools-camera angle, pattern of narrative network and mis-en-scene developed by Yale University so as to justify how the set of patterns employed in this visual discourse appeals to its theme in a particular scene. In addition, haptic visuality is studied with special affect. The time denoted, in the paper, for shots is in descending order in the Netflix from the total running time of one hour and fifty-three minutes. Thematically, the entire project focuses on how individuals can make a difference with their selfless efforts even in the face of a global crisis. Shot in eight different countries with nine stories, the Director, Orlando von Einsiedel in a great narrative maneuver, demonstrates the stirring individual grit and compassion with selfless efforts of the unsung heroes, born in the crises. It can also be analyzed as the message towards the global community with the information dissemination for the preparedness of viral emergence next. What makes this documentary poignant and all inspiring is its intimate telling of the stories of the noble heroes through visual discourse amidst the challenging health emergency and trauma. The study is going to be significant because it not only gives the world view of the sweeping chronicle of the global fight against the pandemic but also prepares every individual for resilience with the hope that humans can triumph over the crisis in unison.